2010
DOI: 10.1016/j.jpainsymman.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Mortality Rates: How Is Palliative Care Taken into Account?

Abstract: Proliferation of, and variability among, hospital mortality measures creates a challenge for hospital administrators. PC and hospice leaders need to educate themselves and their hospital administrators about the extent to which these mortality rates take end-of-life care into account. At the national level, PC and hospice leaders should take advantage of opportunities to engage these mortality raters in conversation about possible changes in their methods and to conduct further research on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…A point prevalence survey in 3 Australian hospitals showed that 35% were classifiable as “requiring a palliative approach” but only 22% of those patients were referred for palliative care – overall, a total of 7.7% . A point prevalence study in Norway showed that 36% of all patients were classified as “palliative” as defined by “advanced, serious, chronic disease with limited life expectancy and symptom relief as the main goal of treatment.” The V66.7 code used in our study is uniformly recognized as the only diagnosis code specifically associated with palliative care, but may be used differently by hospital raters of quality . Regardless of methodology, these data show that the use of palliative care remains low in a disease with a high symptom burden.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A point prevalence survey in 3 Australian hospitals showed that 35% were classifiable as “requiring a palliative approach” but only 22% of those patients were referred for palliative care – overall, a total of 7.7% . A point prevalence study in Norway showed that 36% of all patients were classified as “palliative” as defined by “advanced, serious, chronic disease with limited life expectancy and symptom relief as the main goal of treatment.” The V66.7 code used in our study is uniformly recognized as the only diagnosis code specifically associated with palliative care, but may be used differently by hospital raters of quality . Regardless of methodology, these data show that the use of palliative care remains low in a disease with a high symptom burden.…”
Section: Discussionmentioning
confidence: 68%
“…34 The V66.7 code used in our study is uniformly recognized as the only diagnosis code specifically associated with palliative care, but may be used differently by hospital raters of quality. 35 Regardless of methodology, these data show that the use of palliative care remains low in a disease with a high symptom burden.…”
Section: Discussionmentioning
confidence: 92%
“…The care provided must be aimed only at relieving pain and discomfort for the palliative care code to be applicable”(32). Further clarification regarding the incorporation of palliative care codes by several national healthcare databases has been described by Cassel et al(33). ICD9-CM code V66.7 has previously been shown to accurately identify palliative care services in stroke patients with 81% sensitivity and 97% specificity(5).…”
Section: Methodsmentioning
confidence: 99%
“…This code has previously been reported to have high sensitivity and specificity for identifying patients who underwent withdrawal of life-sustaining therapy, 6 but there is concern that its use is not specific for patients who receive specialized palliative care, and that it is largely used to capture the subset of palliative care patients who are actively dying. 7,8 Given the increasing use of this code and prior concerns about its utility, 9,10 we performed a single-center validation study to determine the sensitivity and specificity of the V66.7 code for determining whether hospitalized patients did or did not receive specialized palliative care consultation.…”
Section: Introductionmentioning
confidence: 99%